Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.concog.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

The mindful eye: Smooth pursuit and saccadic eye movements in meditators and non-meditators

Abstract: Cultivated, but not dispositional, mindfulness is associated with improved attention and sensorimotor control as indexed by SPEM and AS tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…A recent study of meditators and non-meditators showed that cultivated mindfulness is associated with fewer saccadic intrusions in SPEM. One could conceivably argue that cannabis has a similar effect for patients with psychosis through similar cognitive and attentional processes, thereby normalising SPEM 45 . It is worth noting, however, that the Kumari and colleagues findings were related to saccadic intrusions during SPEM, finding no difference in SPEM velocity between meditators and non-meditators and, therefore, does not suggest that SPEM velocity, as indexed in our study is of itself is a measure of cultivated mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of meditators and non-meditators showed that cultivated mindfulness is associated with fewer saccadic intrusions in SPEM. One could conceivably argue that cannabis has a similar effect for patients with psychosis through similar cognitive and attentional processes, thereby normalising SPEM 45 . It is worth noting, however, that the Kumari and colleagues findings were related to saccadic intrusions during SPEM, finding no difference in SPEM velocity between meditators and non-meditators and, therefore, does not suggest that SPEM velocity, as indexed in our study is of itself is a measure of cultivated mindfulness.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported a relation between mindfulness meditation expertise and reduction of mind-wandering episodes, with mind-wandering being assessed both in terms of frequency and intensity through thought-probes and self-reports methods [107], or indexed by deactivation of the DMN in neuroimaging studies [108]. Moreover, it has recently been found that expert meditators show better attention and ocular sensorimotor control than novices during smooth pursuit and antisaccade tasks [109], a finding in line with the suggestion that attention and eye movement processes could involve functionally overlapping brain areas [110].…”
Section: Discussionmentioning
confidence: 99%
“…Eye movement has also been previously employed in studies to evaluate meditation attention. Kumari et al used infrared oculography to examine mindfulness meditation, particularly performance during smooth pursuit eye movements, antisaccade tasks, and prosaccade tasks [38]. They measured eye closure, obtained electroencephalograms during focused breathing, and extracted eye-movement-derived ocular data from electroencephalogram signals instead of using a standard multielectrode electrooculography montage to monitor ocular data.…”
Section: Discussionmentioning
confidence: 99%